Performance of Hydrothermally Prepared NiMo Dispersed on Sulfated Zirconia Nano-Catalyst in The Conversion of Used Palm Cooking Oil into Jet Fuel Range Bio-Hydrocarbons - Wijaya, Karna; Saviola, Aldino Javier; Amin, Amalia Kurnia; Vebryana, Marini Fairuz; Bhagaskara, Adyatma; Ekawati, Hilda Anggita; Ramadhani, Saffana; Saputra, Dita Adi; Agustanhakri, Agustanhakri (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
Human efforts to overcome environmental problems from using fossil fuels continue, such as hydroconversion of biomass into bio-jet fuel. Research on producing a jet fuel range of bio-hydrocarbons from used palm cooking oil catalyzed by sulfated zirconia impregnated with nickel-molybdenum bimetal has been successfully conducted. The hydrothermal method synthesized the nano-catalyst material in the sulfation and impregnation processes. The hydroconversion process was carried out at atmospheric pressure and a temperature of 300–600 °C for 2 h with a hydrogen gas flow rate of 20 mL/min and a catalyst-to-feed ratio of 1:100 (wt%). Compared with zirconia and sulfated zirconia, NiMo-impregnated sulfated zirconia showed the best activity and selectivity in bio-jet fuel production with liquid product and selectivity of 61.07% and 43.49%, respectively. This catalyst also performed well in three consecutive runs, with bio-jet fuel selectivity in the second and third runs of 51.68% and 30.86%, respectively. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).